Oxytocin decreases diurnal and nocturnal arterial blood pressure in the conscious unrestrained spontaneously hypertensive rat. Issue 2 (June 2016) - Gutkowska, Jolanta; Aliou, Yessoufou; Lavoie, Julie L.; Gaab, Katie; Jankowski, Marek; Broderick, Tom L.
Abstract: In this study, we assessed the effects of oxytocin (OT) on mean arterial blood pressure (MAP), heart rate (HR), and locomotor activity (LA) in male spontaneous hypertensive rats (SHR) and Sprague-Dawley (SDR) controls using telemetry. OT was given by intravenous injections of 0.1, 0.2 or 0.4 mg/kg to assess short term acute effects or by daily subcutaneous injections of 0.5 or 1.0 mg/kg for 5 days. Compared to the saline infusion, (i) intravenous OT, regardless of concentration, increased MAP in SHR and SDR, (ii) HR increased, but was periodically lower in both strains with 0.2 or 0.4 mg/kg, and (iii) no effects of OT on LA were observed. Subcutaneous injections demonstrated that (i) 1.0 mg/kg for 5 days lowered diurnal MAP and HR in SDR and SHR, persisting for 6 days, (ii) 1.0 mg/kg decreased nocturnal HR in SDR, (iii) 0.5 and 1.0 mg/kg decreased MAP with minor effects on HR in the SHR, and lastly (iv) OT decreased LA mainly during the diurnal cycle in both strains. Our main results show that OT induces significant beneficial effects on cardiovascular function over several diurnal and nocturnal cycles in the SHR, with the most prominent effect being a robust decrease in MAP.